How The Students Perceive On The Use Of Cooperative Learning In Teaching Speaking - Netty Huzniati Andas (EDUCATIO : Journal of Education, 2018)
Cooperative Learning is teaching method in which students work in a small group to achieve a joint goal. This study aimed to investigate students’ perception toward Cooperative Learning in improving their ability to speak. This research employed qualitative research design. There were six (6) intermediate students in Progress English Course Center as participants in this research. Those participants were selected through purposive sampling technique. To gain the data, interview and students’ field diary were used. The result of both questionnaire and students’ field diary were positive, which means students showed a good response when teacher taught them by using Cooperative Learning. Students no longer felt anxious in speaking, they were not afraid anymore to express their idea, and they become an active participant in group discussion. This study concluded that students supported the use of Cooperative Learning on teaching speaking.